LOW TEMPERATURE OXYGEN ISOTOPIC FRACTIONATION IN THE URANINITE-UO3-CO2-H2O SYSTEM - Fayek M.; Kyser T.K. (My University, 2000)
Oxygen-isotope fractionation factors for uraninite-water and UO3-water were determined from a series of uraninite-CO2 and UO3-CO2 exchange experiments between 100 and 300°C. The measured fractionation factors are similar to the theoretical fractionation factors of Hattori and Halas (1982) at high temperatures and Zheng (1991) at low temperatures and are nonlinear over the temperature range examined. Regression through these curve gives 1000 ln αUO2-H2O = 16.58 (106/T2) - 77.52 (103/T) + 77.48, 1000 ln αUO3-H2O = -2.21 (106/T2) + 25.06 (103/T) - 45.90 with 2σ errors of +/-2.5%%. Diffusion coefficients of oxygen with temperature for uraninite and UO3 can be represented by D(uraninite) = 3.1 x 10-10 exp (-63981/RT) and D(UO3) = 1.3 x 10-15 exp (-21,197/RT), where the activation energies for uraninite and UO3 are 64.0 +/- 0.2 kcal/mole and 21.2 +/- 0.2 kcal/mol, respectively. Exceptionally low δ18O values of natural uraninites (i.e., -32%% to -19.5%%) from unconformity-type uranium deposits in Saskatchewan, in conjunction with theoretical and experimental uraninite-water and UO3-water fractionation factors, suggest that primary uranium mineralization is not in oxygen isotopic equilibrium with coeval clay and silicate minerals. The low δ18O values have been interpreted as having resulted from the low temperature recrystallization of primary uranium mineralization in the presence of relatively modern meteoric fluids having δ18O values of ca. -18%%, despite petrographic and U-Pb isotope data that indicate limited alteration. Therefore, it appears that uranium minerals can exchange oxygen isotopes with later fluids, with only limited actinide remobilization and minor disturbances to their original chemical compositions and textures.